The effect of cultural capital on the physical fitness level of a Chinese older adult population: chain mediation of household income and stockpiling of physical fitness goods - Zhao, Deqiang; Wang, Yibei; Zhang, Aoyu; He, Jin; Gao, Yibo; Chen, Xiaoxiao; Jiang, Lupei; Zhang, Yanfeng (Frontiers in Public Health, 2024)
BackgroundHealth behaviors of older people are influenced by many factors, and physical activity are important lifestyle behaviors that promote healthy aging.PurposeThis study is to analyze the intrinsic mechanism of the influence of cultural capital on the physical fitness level of older people, and to provide a theoretical basis for the improvement of the differences in physical fitness level caused by the differences in physical fitness concepts of the classes brought about by cultural capital, and the unequal distribution of resources.MethodsThe subjects of this study were derived from people over 60 years old in the 2020 China National Fitness Activity Status Survey, and a total of 20,896 samples were obtained using the principle of multi-stage stratified random sampling. The dependent variable was assessed by the Physical Activity Rating Scale (PARS-3) to calculate the physical activity level score of the older adult population. Pearson correlation analysis and stratified regression methods were used to analyze and explore the factors influencing the physical fitness level of sport older adult people, followed by quantile regression to explore the distribution of the influence of institutional cultural capital in different physical fitness levels. The use of quantile regression not only provided a robust test of the results of stratified linear regression, but also analyzed the differential effects of institutional cultural capital among individuals with different fitness levels. Finally, Bootstrap methods were used to test the mediating effects of household income and physical cultural capital.ResultsInstitutional cultural capital (p < 0.01), household income (p < 0.01), physical cultural capital (p < 0.01), and health status (p < 0.01) are all conducive to improving fitness levels among older people. Family income (95%CI = [0.467, 0.235]) and material cultural capital (95%CI = [0.199, 0.291]) play a chain mediating role.ConclusionCultural capital has a positive impact on the health of older people, mediated by household income and stocks of sporting goods. An increase in the level of cultural capital of older persons is beneficial to the improvement of health perception. Therefore, it is possible to promote the improvement of physical fitness among older people through the enhancement of their cultural capital and to realize healthy aging.